High-temperature-resistant anti-salt deposition coating for quench tower and preparation method thereof
By using a high-temperature anti-salt coating composed of graphite powder, tungsten phosphide, fluorinated bell and other components on the quench tower, the problem of salt forming in the inner wall of the quench tower is solved, the excellent performance of the paint in a high-temperature environment is achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202510064184.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
During operation, the accumulation of chloride, sulfide and sulfate and other substances in the quench tower will cause serious salt formation on the inner wall, which will affect the continuity and stability of the incineration system and increase operating costs.
A high-temperature anti-salt coating for quench towers is used. The coating consists of graphite powder, tungsten phosphide, fluorinated bells, chromium oxide, antioxidant, binder, dispersant and deionized water. It is prepared by ball milling and stirring, forming a coating with excellent comprehensive performance.
The coating has good hardness, high temperature resistance, adhesion, salt resistant and salt spray resistance under high temperature environments, which significantly reduces the formation and accumulation of salt scale in the inner wall of the quench tower and extends the service life of the equipment.
Smart Images

Figure BDA0005243749780000071 
Figure BDA0005243749780000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a high-temperature resistant anti-salting coating for a quenching tower and a preparation method thereof. Background Art
[0002] The quench tower is an important equipment in the hazardous waste incineration system. Its main function is to quickly cool down and remove dust from high-temperature flue gas. After the temperature of the high-temperature flue gas is reduced to 200°C in the quench tower, the re-synthesis of dioxins can be effectively controlled. At the same time, it can effectively wash and absorb pollutants such as sulfur dioxide, hydrogen chloride, and a small amount of nitrogen oxides in the acidic gas. However, during the operation of the quench tower, chlorides, sulfides, sulfates and other substances will inevitably be produced, resulting in serious salt deposition on the inner wall of the quench tower, and the furnace has to be shut down to clean salt and ash. This not only seriously affects the continuity and stability of the incineration system, but also increases the operating costs of hazardous waste enterprises. Effectively solving the problem of coking on the inner wall of the quench tower has become an imminent practical problem for all hazardous waste enterprises.
[0003] In order to solve the above technical problems, the present invention provides a high temperature resistant anti-salting coating suitable for the high temperature environment of the quench tower, while reducing the formation and accumulation of salt scale on the inner wall thereof. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, one of the objects of the present invention is to provide a high-temperature resistant anti-salt coating for a quenching tower, which has excellent comprehensive performance, good hardness, high temperature resistance, adhesion, salt resistance and salt spray resistance.
[0005] The second object of the present invention is to provide a method for preparing a high temperature resistant anti-salting coating for a quenching tower, which has simple steps and is easy to operate.
[0006] One of the purposes of the present invention is achieved by the following technical solution:
[0007] A high-temperature resistant anti-salting coating for a quenching tower comprises the following raw materials in parts by weight: 30-60 parts of graphite powder, 5-10 parts of tungsten phosphide, 5-10 parts of terbium fluoride, 8-15 parts of chromium oxide, 3-5 parts of antioxidant, 15-20 parts of binder, 1-3 parts of dispersant and 3-7 parts of deionized water.
[0008] Furthermore, the raw materials include the following parts by weight: 45 parts of graphite powder, 8 parts of tungsten phosphide, 6 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of antioxidant, 19 parts of binder, 2 parts of dispersant, and 5 parts of deionized water.
[0009] Furthermore, the graphite powder consists of graphite powder A and graphite powder B; the mass ratio of the graphite powder A to the graphite powder B is 1:(1-2).
[0010] Furthermore, the average particle size of the graphite powder A is 50-80 μm, and the average particle size of the graphite powder B is 5-15 μm.
[0011] Furthermore, the antioxidant is silicon powder, the binder is silica sol, and the dispersant is sodium tripolyphosphate.
[0012] Furthermore, the SiO 2 The mass concentration is 25-35wt%.
[0013] Furthermore, the particle size of the silicon powder is 1 to 5 μm.
[0014] The second object of the present invention is achieved by adopting the following technical solution:
[0015] The preparation method of the high temperature resistant anti-salting coating for the quenching tower comprises the following steps:
[0016] (1) weighing the raw materials according to the weight ratio, mixing graphite powder, tungsten phosphide, terbium fluoride, chromium oxide and antioxidant, and ball milling to obtain a mixture;
[0017] (2) The mixture of step (1), a binder, a dispersant and deionized water are mixed and stirred.
[0018] Furthermore, the ball milling time in step (1) is 1 to 3 hours; and the ball-to-material ratio during the ball milling process is (25 to 35):1.
[0019] Furthermore, in step (2), the stirring speed is 800-1000 rpm, and the stirring time is 2-3 h.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides a high-temperature resistant anti-salting coating for a quenching tower, wherein the coating formula contains ingredients such as tungsten phosphide, terbium fluoride, and graphite powder, and the graphite powder is composed of two graphite powders with different average particle sizes. The synergistic effect of terbium fluoride and tungsten phosphide in the formula can enhance the salt resistance of the coating. Specifically, tungsten phosphide has a low affinity for sulfur atoms, thereby reducing the adhesion and accumulation of sulfides, sulfates, etc. on the surface of the coating, thereby enhancing the salt resistance of the coating; terbium fluoride has a high surface energy and thus has low adhesion. This characteristic can promote the shedding of salt slag on the surface of the coating, thereby enhancing the salt resistance of the coating. In addition, the use of two graphite powders with different average particle sizes in the formula can form a graphite powder system with a reasonable particle size distribution, which not only ensures the stability of the coating and the performance of the coating, but also improves the adhesion of the coating.
[0022] 2. The high temperature resistant and anti-salt coating of the present invention has excellent comprehensive performance, and has good hardness, high temperature resistance, adhesion, salt resistance, and salt spray resistance.
[0023] 3. The present invention provides a method for preparing a high-temperature resistant anti-salting coating for a quenching tower. The preparation method has simple steps and is easy to practice. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0025] In the embodiment of the present invention, the average particle size of graphite powder A is 50-80 μm, the average particle size of graphite powder B is 5-15 μm; and the particle size of silicon powder is 1-5 μm.
[0026] Example
[0027] Example 1
[0028] This embodiment provides a high temperature resistant anti-salt coating for a quenching tower, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder, 8 parts of tungsten phosphide, 6 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 30wt%.
[0029] This embodiment also provides a method for preparing the high temperature resistant anti-salting coating for the quenching tower, which is as follows:
[0030] (1) Weighing the raw materials according to the above weight ratio, mixing graphite powder, tungsten phosphide, terbium fluoride, chromium oxide and silicon powder, and ball milling for 2 hours at a ball-to-material ratio of 30:1 to obtain a mixture;
[0031] (2) The mixture of step (1), silica sol, sodium tripolyphosphate and deionized water were mixed and stirred at a speed of 900 rpm for 2.5 hours.
[0032] Example 2
[0033] This embodiment provides a high temperature resistant anti-salt coating for a quenching tower, which is composed of the following raw materials in parts by weight: 60 parts of graphite powder, 10 parts of tungsten phosphide, 10 parts of terbium fluoride, 15 parts of chromium oxide, 5 parts of silicon powder, 20 parts of silica sol, 3 parts of sodium tripolyphosphate, and 7 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:2; SiO in the silica sol is 100 parts of tungsten phosphide, 10 parts of terbium fluoride, 15 parts of chromium oxide, 5 parts of silicon powder, 20 parts of silica sol, 3 parts of sodium tripolyphosphate, and 7 parts of deionized water. 2 The mass concentration is 35wt%.
[0034] This embodiment also provides a method for preparing the high temperature resistant anti-salting coating for the quenching tower, which is as follows:
[0035] (1) Weighing the raw materials according to the above weight ratio, mixing graphite powder, tungsten phosphide, terbium fluoride, chromium oxide and silicon powder, and ball milling for 1 hour at a ball-to-material ratio of 35:1 to obtain a mixture;
[0036] (2) The mixture of step (1), silica sol, sodium tripolyphosphate and deionized water were mixed and stirred at a speed of 1000 rpm for 2 h.
[0037] Example 3
[0038] This embodiment provides a high temperature resistant anti-salt coating for a quenching tower, which is composed of the following raw materials in parts by weight: 30 parts of graphite powder, 5 parts of tungsten phosphide, 5 parts of terbium fluoride, 8 parts of chromium oxide, 3 parts of silicon powder, 15 parts of silica sol, 1 part of sodium tripolyphosphate, and 3 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 25wt%.
[0039] This embodiment also provides a method for preparing the high temperature resistant anti-salting coating for the quenching tower, which is as follows:
[0040] (1) Weighing the raw materials according to the above weight ratio, mixing graphite powder, tungsten phosphide, terbium fluoride, chromium oxide and silicon powder, and ball milling for 3 hours at a ball-to-material ratio of 25:1 to obtain a mixture;
[0041] (2) The mixture of step (1), silica sol, sodium tripolyphosphate and deionized water were mixed and stirred at a speed of 800 rpm for 3 hours.
[0042] Comparative Example
[0043] Comparative Example 1
[0044] This comparative example provides a coating, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder, 8 parts of tungsten oxide, 6 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 30wt%.
[0045] The specific preparation method of the coating of this comparative example is the same as that of Example 1.
[0046] Comparative Example 2
[0047] This comparative example provides a coating, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder, 8 parts of tungsten phosphide, 6 parts of terbium oxide, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 30wt%.
[0048] The specific preparation method of the coating of this comparative example is the same as that of Example 1.
[0049] Comparative Example 3
[0050] This comparative example provides a coating, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder, 14 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 30wt%.
[0051] The specific preparation method of the coating of this comparative example is the same as that of Example 1.
[0052] Comparative Example 4
[0053] This comparative example provides a coating, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder, 14 parts of tungsten phosphide, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water. The graphite powder is composed of graphite powder A and graphite powder B in a mass ratio of 1:1; SiO in the silica sol is 1:1. 2 The mass concentration is 30wt%.
[0054] The specific preparation method of the coating of this comparative example is the same as that of Example 1.
[0055] Comparative Example 5
[0056] This comparative example provides a coating, which is composed of the following raw materials in parts by weight: 45 parts of graphite powder B, 8 parts of tungsten phosphide, 6 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of silicon powder, 19 parts of silica sol, 2 parts of sodium tripolyphosphate, and 5 parts of deionized water, wherein the mass concentration of silica sol is 30wt%.
[0057] The specific preparation method of the coating of this comparative example is the same as that of Example 1.
[0058] Test example
[0059] The properties of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were investigated, and the specific indicators and detection methods were as follows:
[0060] ① Pencil hardness: The pencil hardness of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to GB / T 6739-2006. The results are shown in Table 1;
[0061] ② Adhesion: The adhesion of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to GB / T 1720-2020. The results are shown in Table 1;
[0062] ③ Impact strength: The impact strength of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to GB / T 1732-2020. The results are shown in Table 1;
[0063] ④ High temperature resistance: The high temperature resistance of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to GB / T 1735-2009. The temperature was increased at a heating rate of 5°C / min to test the temperature at which cracking and shedding occurred. The results are shown in Table 1.
[0064] ⑤ Salt spray resistance: The salt spray resistance of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to GB / T 1771-2007. The results are shown in Table 1;
[0065] ⑥ Salt resistance: According to the conventional method, the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were used to prepare coatings on the heated surface of a quenching tower. The coating thickness was 150 μm. The salting of the coatings was tested after one month of service in the quenching tower. The results are shown in Table 1.
[0066] Table 1
[0067]
[0068]
[0069] As can be seen from Table 1, the coatings prepared in Examples 1 to 3 of the present invention have high hardness, good adsorption capacity, high impact strength, and excellent salt spray resistance and salt resistance under high temperature service of 1900-2000°C.
[0070] Compared with Examples 1 to 3, the salt resistance of the coatings obtained in Comparative Examples 1 to 4 is significantly reduced. Analysis shows that Comparative Example 1 uses tungsten oxide instead of tungsten phosphide; Comparative Example 2 uses terbium oxide instead of terbium fluoride; Comparative Example 3 omits tungsten phosphide and increases the amount of terbium fluoride; Comparative Example 4 omits terbium fluoride and increases the amount of tungsten phosphide, and the salt resistance of the obtained coating is significantly reduced. The above results show that the synergistic effect of terbium fluoride and tungsten phosphide can enhance the salt resistance of the coating. Further analysis shows that tungsten phosphide has a low affinity for sulfur atoms, which can reduce the adhesion and accumulation of sulfides, sulfates, etc. on the surface of the coating, thereby enhancing the salt resistance of the coating; terbium fluoride has a high surface energy and therefore has a low adhesion. This characteristic can promote the shedding of salt residue on the surface of the coating, thereby enhancing the salt resistance of the coating.
[0071] Compared with Examples 1 to 3, the adhesion of the coating obtained in Comparative Example 5 is reduced. Analysis shows that Comparative Example 5 only uses graphite powder B with an average particle size of 5 to 15 μm. The above results show that the combination of two graphite powders with different average particle sizes can form a graphite powder system with a reasonable particle size distribution, which not only ensures the stability of the coating and the performance of the coating, but also improves the adhesion of the coating. In summary, the high temperature resistant and anti-salting coating of the present invention has excellent comprehensive performance, and has good hardness, high temperature resistance, adhesion, salt resistance and salt spray resistance.
[0072] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high temperature resistant anti-salting coating for a quenching tower, characterized in that: The invention comprises the following raw materials in parts by weight: 30-60 parts of graphite powder, 5-10 parts of tungsten phosphide, 5-10 parts of terbium fluoride, 8-15 parts of chromium oxide, 3-5 parts of antioxidant, 15-20 parts of binder, 1-3 parts of dispersant and 3-7 parts of deionized water.
2. The high temperature resistant anti-salting coating for a quenching tower according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 45 parts of graphite powder, 8 parts of tungsten phosphide, 6 parts of terbium fluoride, 12 parts of chromium oxide, 4 parts of antioxidant, 19 parts of binder, 2 parts of dispersant and 5 parts of deionized water.
3. The high temperature resistant anti-salting coating for a quenching tower according to claim 1 or 2, characterized in that: The graphite powder consists of graphite powder A and graphite powder B; the mass ratio of the graphite powder A to the graphite powder B is 1:(1-2).
4. The high temperature resistant anti-salting coating for a quenching tower according to claim 3, characterized in that: The average particle size of the graphite powder A is 50-80 μm, and the average particle size of the graphite powder B is 5-15 μm.
5. The high temperature resistant anti-salting coating for a quenching tower according to claim 1 or 2, characterized in that: The antioxidant is silicon powder, the binder is silica sol, and the dispersant is sodium tripolyphosphate.
6. The high temperature resistant anti-salting coating for a quenching tower according to claim 5, characterized in that: The mass concentration of SiO2 in the silica sol is 25-35wt%.
7. The method for preparing the high temperature resistant anti-salting coating for a quenching tower according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) weighing the raw materials according to the weight ratio, mixing graphite powder, tungsten phosphide, terbium fluoride, chromium oxide and an antioxidant, and ball milling to obtain a mixture; (2) The mixture of step (1), a binder, a dispersant and deionized water are mixed and stirred.
8. The method for preparing the high temperature resistant anti-salting coating for a quenching tower according to claim 7, characterized in that: The ball milling time in step (1) is 1 to 3 hours; the ball-to-material ratio in the ball milling process is (25 to 35):
1.
9. The method for preparing the high temperature resistant anti-salting coating for a quenching tower according to claim 7, characterized in that: The stirring speed in step (2) is 800-1000 rpm, and the stirring time is 2-3 h.
Citation Information
Patent Citations
Solar photothermal conversion material and preparation method thereof
CN109206553A
Aerogel high temperature radiation resistant inorganic coating
CN109385120A
Anti-coking coating and preparation process thereof
CN114196238A
Anti-sticking coating for oxygen lance of converter and preparation method of anti-sticking coating
CN114369381A
Micro-nano multi-scale anti-coking wear-resistant coating, composite material and preparation method thereof
CN115160835A